Which skeletal pattern should consider the correlation between the tongue volume versus the upper airway and craniofacial structure? A cross-sectional descriptive study in Vietnamese - Lam N. Le; Loc T. Tan; Trinh T. N. Nguyen; Khanh P. V. Le (Journal of Orthodontic Science)
CONTEXT: Numerous studies worldwide have shown that there is a significant difference between tongue volume and pharyngeal airway volume in skeletal patterns Class I, Class II, and Class III. It is closely related to the position, size of the jaw bone and volume of the oral cavity. This distinction plays an important role in orthodontic evaluation and treatment planning, especially in patients at risk for airway obstruction during sleep. OBJECTIVE: To evaluate the volume of the tongue and pharyngeal airway in adults with different malocclusion conditions, in order to clarify the relationship between tongue volume, pharyngeal airway volume and oral cavity volume. MATERIAL AND METHODS: A cross-sectional descriptive prospective study analysis was conducted on 120 patients with varying skeletal patterns who sought examination and treatment at the Department of Dentistry and Maxillofacial Surgery, Can Tho University of Medicine and Pharmacy Hospital. Imaging data from these patients were used to evaluate the volume of the tongue and pharyngeal airway in adults with different malocclusion conditions. RESULTS: The average volumes of TV (Tongue volume) and TPV (Total pharynx volume) in Class III malocclusion were the largest, with values of 57820.86 cm3 and 28385.33 cm3, respectively. In contrast, the smallest volumes were observed in Class II, with values of 50380.48 cm3 and 23414.58 cm3, respectively. CONCLUSIONS: An inverse correlation has been established between the TV/OCV (Tongue volume/Oral cavity volume) ratio and pharyngeal airway volume. This finding suggests that tongue volume, oral cavity volume, and their ratio influence airway patency. Understanding the relationship between the tongue and the airway in orthodontic treatment planning, particularly in improving airway space for patients with Class II malocclusion.